Being able “to look up”. Parenting in poverty and the social work intervention - Sanfelici, Mara; Gui, Luigi (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The aim of this article is to explore how social workers represent the experience of parenting in conditions of economic precariousness, and the role of social work in supporting these families. Interviews were administered to a sample of social workers in different Italian regions in both public and non-profit agencies. The grounded theory method, coherent with the interpretative paradigm chosen in this research, guided the process of data collection and data analysis. Our findings reveal that the majority of the social workers recognized the impact of poverty on families’ lives, however this aspect was not always taken into account in the helping process with low income parents. Several variables, both at the individual and the organizational level, seemed to hamper the possibility to “look up” from direct practice with individuals only, and to be involved in policy-shaping and in community work to address roots of family troubles in the wider social context. The analysis is useful to show how poverty of the families and poverty of resources dedicated to them within the welfare state system are interconnected issues that should not be viewed as background factors, but as variables that influence in various ways the decisions made everyday in social services. We identify the need for improvement in the institutional framework of public services and in social work education.